PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN RISIKO SEBAGAI VARIABEL MODERASI - Sulistiawati Sulistiawati; Umi Muawanah (Jurnal Ekonomi dan Manajemen, 2018)
The purpose of this research are to analysis what are risk management strengthen relationshipbetween independent commissioner and audit committee to financial performance. Dependenvariable is financial performance, independen variables are independent commissioner and auditcommittee, while the moderation variable is risk management. The samples are 96 period ofNasional Private Banking Company are listed in Indonesia stock exchange in the period 2012-2016. Analysis technique used Moderated Regression Analysis (MRA) with software SPSS 20.The result of the study indicates that risk management not moderated variable wich strengthenrelationship between independent commissioner to financial performance while risk managementis moderated variable wich strengthen relationship between audit commitee to financialperformance.